1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1709::aid-immu1709>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The oncogene product Vav is a crucial regulator of primary cytotoxic T cell responses but has no apparent role in CD28-mediated co-stimulation

Abstract: The guanine nucleotide-exchange factor Vav is a regulator of antigen-mediated cytoskeletal reorganization required for receptor clustering, proliferation and thymic selection. Moreover, Vav has been identified as a major substrate in the CD28 signal transduction pathway and overexpression of Vav enhances TCR-mediated IL-2 secretion in T cells. Here we show that CD3-plus CD28-mediated proliferation and IL-2 production were reduced in vav gene-deficient T cells. However, Vav had no apparent role in phorbol 12-my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…The difference in the ability of Vav1-deficient T cells to proliferate in vivo vs. in vitro may be due to the presence of costimulatory signals in the lymphoid organ, which are absent in a simplified in vitro proliferation assay. In other studies, examination of antiviral responses in Vav1-deficient mice showed decreased primary CD8 cytotoxic T cell responses, although these became normal following secondary restimulation in vitro (39).…”
Section: Vav1 In Peripheral T Cell Functionmentioning
confidence: 78%
“…The difference in the ability of Vav1-deficient T cells to proliferate in vivo vs. in vitro may be due to the presence of costimulatory signals in the lymphoid organ, which are absent in a simplified in vitro proliferation assay. In other studies, examination of antiviral responses in Vav1-deficient mice showed decreased primary CD8 cytotoxic T cell responses, although these became normal following secondary restimulation in vitro (39).…”
Section: Vav1 In Peripheral T Cell Functionmentioning
confidence: 78%
“…Vav-1 -/-mice have reduced numbers of both T and NK T cells, as well as defects in primary cytotoxic T cell responses [24]. Therefore, to generate Vav-1 -/-LAK populations comparable to wild type, before culture we first depleted CD4 + and CD8 + cells from the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50] Vav-deficient T cells were shown to be defective in TCR-induced actin polymerization. 51,52 Low densities of agonist peptides or short-lived peptides induced a transient phosphorylation of Vav in T cells treated with inhibitory doses of peptides, which was accompanied by no detectable actin polymerization.…”
Section: Low-density Tcr Ligand and Apls And Intracellular Signallingmentioning
confidence: 99%